The role of TGFβ signaling in lymphatic endothelial sprout formation - Granroth, Sonja (My University, 2020)
Lymphatic vasculature consists of complex treelike lymphatic vessel networks formed by lymphatic endothelial cells (LECs). The lymphatic vessel network expands via sprouting of LECs from the existing network, i.e. via lymphangiogenesis. Recent studies suggest that Transforming growth factor beta (TGFβ) signaling plays a role in the regulation of LEC sprouting in lymphangiogenesis. However, due to the context-dependent nature of TGFβ signaling, the specific role and mechanisms of TGFβ signaling in lymphatic vessel network formation remain unclear. This thesis project aimed to develop a suitable model for monitoring LEC sprouting in cell culture and to unravel the regulatory effects of TGFβ in LEC sprouting. To investigate the regulatory effects of the TGFβ pathway, I altered TGFβ signaling in LECs by: 1. treating the cell culture acutely or chronically with 1ng/ml TGFβ, or 2. overexpressing components of the TGFβ signaling pathway by transducing LECs with created lentiviral vectors encoding EGFP-SMAD1 and constitutively active TGFβR1. I recorded the migration of LECs for 20 hours in the scratch-wound assay and calculated the amount of formed protrusions, normalizing it to the control sample. For live-imaging, I utilized an epifluorescence microscope equipped with an environmental control chamber and performed image analysis with image analysis software. I observed an increased number of LEC protrusions in response to acute TGFβ, peaking at an 8-hour time point. Interestingly, chronic activation of the TGFβ pathway did not increase the sprouting potency of LECs. Overall, the results suggest that acute TGFβ exposure plays a role in the regulation of LEC sprouting. Additionally, I successfully produced a LEC sprouting study model that can be utilized in the execution of more extensive studies. Further comprehensive research is required to reveal causative molecular mechanisms that TGFβ signaling employs in the regulation of LEC sprouting.
Keywords: lymphatic endothelial cells (LECs), Transforming growth factor beta (TGFβ), lymphangiogenesis, lymphatic endothelial sprouting